Quality Characteristics of Wheat Flour and Fermented Watermelon Seed Flour Blends - Abubakar Ummulkhairu; Akubor P. I.; Rabiu Ibrahim Ajiya; Adamu Hamsatu Sani (Darul Yasin Al Sys, 2026)
Bread quality can be enhanced through the incorporation of nutrient-dense alternative flours, yet evidence on the use of fermented watermelon seed flour remains limited. This study evaluated the quality characteristics of bread produced from wheat flour partially substituted with fermented watermelon seed flour (FWSF). Watermelon seeds were fermented with Saccharomyces cerevisiae for 72 hours, oven-dried at 40°C, milled, and sieved to 0.25 mm, after which the resulting flour was blended with wheat flour at substitution levels of 5%, 10%, 15%, 20%, and 25%. The flour blends were analyzed for proximate composition, phytochemical content, functional properties, and pasting characteristics, while the breads were evaluated for chemical composition, antioxidant activity, protein and starch digestibility, color, physical properties, and sensory attributes. The results showed that FWSF incorporation improved the proximate composition, phytochemical content, functional properties, and pasting characteristics of the flour blends. Antioxidant activity also increased significantly, with FRAP values rising from 0.13 mol/100 g in the control bread to 0.24–0.33 mol/100 g in composite breads, and DPPH values increasing from 21.74 to 36.71 mg AAE/100 g at 25% substitution. Baking loss decreased from 25% in the control to 16.65% in breads containing FWSF, while physical properties remained largely unaffected. Although sensory scores declined progressively with higher substitution levels, the 5% substitution sample recorded the highest taste rating among the composite breads and did not differ significantly (P > 0.05) from the control in overall sensory attributes. General acceptability ranged from 5.45 to 7.25 for composite breads compared with 7.50 for the control. In addition, L*, a*, and b* color values increased with FWSF inclusion, while the browning index decreased slightly. Overall, partial substitution of wheat flour with fermented watermelon seed flour enhanced the nutritional, functional, and antioxidant quality of bread without adversely affecting its physical characteristics, with 5% substitution identified as the most appropriate level based on improved quality attributes and consumer acceptability.